2021
DOI: 10.1186/s12877-021-02204-y
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational support and subjective wellbeing among oldest-old in China: the moderating role of economic status

Abstract: Backgrounds The oldest-old population is increasing sharply in China, and intergenerational support has been their primary source of caregiving. Although intergenerational support has been found to be associated with wellbeing of older people in previous study, most analysis were from the perspective of children’s characteristics and exchange patterns. This study aims to investigate the impact of different types of intergenerational support on subjective wellbeing among Chinese oldest-old and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 37 publications
5
29
0
1
Order By: Relevance
“…Community environment was another residence condition that increased life satisfaction in old age the most, in line with the literature [ 16 , 17 , 31 ]. Older adults’ community environment is often kept sanitary and clean so that people can enjoy a healthy and comfortable environment.…”
Section: Discussionsupporting
confidence: 83%
“…Community environment was another residence condition that increased life satisfaction in old age the most, in line with the literature [ 16 , 17 , 31 ]. Older adults’ community environment is often kept sanitary and clean so that people can enjoy a healthy and comfortable environment.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings on the significant associations of anxiety symptoms with female sex and poor financial status are consistent with elevated risk of anxiety symptoms in older women and socioeconomically disadvantageous older adults in earlier studies ( 55 57 ). Because family members are a significant source of social support for older Chinese adults and family support plays an important role in the mental well-being of older Chinese adults ( 58 60 ), our finding on the significantly higher risk of anxiety symptoms in older adults without a good family relationship is expected. In general, rural older adults are more likely to develop anxiety symptoms than urban older adults because of their lower socioeconomic status and the inadequate health service resources in rural regions ( 4 ).…”
Section: Discussionmentioning
confidence: 75%
“…Older individuals with higher levels of perceived social support have more psychological resources and are able to call on their psychological resources more effectively to buffer the negative effects of stress or adversity on their mental health. Another study further showed that receiving emotional support promoted parents’ psychological health among all combinations of support, and receiving all the three types of financial, instrumental and emotional support together raised their subjective wellbeing most [ 52 ]. In the current study, perceived social support was found to protect against the psychological distress of older adults.…”
Section: Discussionmentioning
confidence: 99%